1999
DOI: 10.1021/es9812195
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Bioconcentration Factors and Sediment Partition Coefficients in Arctic Seas Subject to Contamination from Dumped Nuclear Wastes

Abstract: The disposal of large quantities of radioactive wastes in Arctic Seas by the former Soviet Union has prompted interest in the behavior of long-lived radionuclides in polar waters. Previous studies on the interactions of radionuclides prominent in radioactive wastes have focused on temperate waters; the extent to which the bioconcentration factors and sediment partitioning from these earlier studies could be applied to risk assessment analyses involving high latitude systems is unknown. Here we present concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 11 publications
5
32
3
Order By: Relevance
“…Our measurements of the bioconcentration factor of radiocesium in the phytoplankton were similar to previous studies (range of 10 to 100; IAEA 1985, Fisher et al 1999, indicating that little Cs was available to phytoplankton. Such a low BCF was generally considered to be due to the high competing K + concentration in the ambient seawater, although our preliminary study indicated that the bioconcentration factor determined at a much lower K + concentration did not affect radiocesium BCF in the algal cells.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our measurements of the bioconcentration factor of radiocesium in the phytoplankton were similar to previous studies (range of 10 to 100; IAEA 1985, Fisher et al 1999, indicating that little Cs was available to phytoplankton. Such a low BCF was generally considered to be due to the high competing K + concentration in the ambient seawater, although our preliminary study indicated that the bioconcentration factor determined at a much lower K + concentration did not affect radiocesium BCF in the algal cells.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the Cs concentration in piscivorous fishes was found to be greater than its concentration in planktivorous and benthivorous fishes, implying a possibility of biomagnification at the top trophic level (Forseth et al 1991, Rowan & Rasmussen 1994, Kasamatsu & Ishikawa 1997. The bioconcentration factor of Cs in seabirds from Arctic regions was also higher than the bioconcentration in invertebrates and seaweeds, although there was a considerable variation of bioconcentration factors within each taxonomic group (Fisher et al 1999). Thus, based on available evidence (Watras & Bloom 1992), Cs and Hg are the only trace elements which show biomagnification at the top level of food chain.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, CFs of 137 Cs in various brown macroalgae varied up to 100 % and in mollusks up to 67 % in a study following radioactive waste disposal in Arctic seas (Fisher et al, 1999). The variation of CF values of 137 Cs in green mussels -Perna viridis -has been also related to body size, water pumping rate, and salinity (Ke et al, 2000).…”
Section: Cesium In Macroalgae and Musselsmentioning
confidence: 99%